Hepatocellular-Targeted mRNA Delivery Using Functionalized Selenium Nanoparticles In Vitro - Dhireshan Singh; Moganavelli Singh (MDPI AG, 2021)
Selenium's (Se) chemopreventative and therapeutic properties have attracted attention in nanomedicine. Se nanoparticles (SeNPs) retain these properties of Se while possessing lower toxicity and higher bioavailability, potentiating their use in gene delivery. This study aimed to formulate SeNPs for efficient binding and targeted delivery of FLuc-mRNA to hepatocellular carcinoma cells (HepG2) in vitro. The colorectal adenocarcinoma (Caco-2) and normal human embryonic kidney (HEK293) cells that do not have the asialoorosomucoid receptor (ASGPR) were utilized for comparison. SeNPs were functionalized with chitosan (CS), polyethylene glycol (PEG), and lactobionic acid (LA) for ASGPR targeting on HepG2 cells. Nanoparticles (NPs) and their mRNA-nanocomplexes were characterized by Fourier transform infra-red (FTIR) and UV-vis spectroscopy, transmission electron microscopy (TEM), and nanoparticle tracking analysis (NTA). Gel and fluorescence-based assays assessed the NP's ability to bind and protect FLuc-mRNA. Cytotoxicity was determined using the -(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, while transgene expression was evaluated using the luciferase reporter gene assay. All NPs appeared spherical with sizes ranging 57.2-130.0 nm and zeta potentials 14.9-31.4 mV. NPs bound, compacted, and protected the mRNA from nuclease digestion and showed negligible cytotoxicity in vitro. Targeted gene expression was highest in the HepG2 cells using the LA targeted NPs. These NPs portend to be efficient nanocarriers of nucleic acids and warrant further investigation.